2013
DOI: 10.1111/1365-2656.12159
|View full text |Cite
|
Sign up to set email alerts
|

Linking manipulative experiments to field data to test the dilution effect

Abstract: Summary1. The dilution effect, the hypothesis that biodiversity reduces disease risk, has received support in many systems. However, few dilution effect studies have linked mechanistic experiments to field patterns to establish both causality and ecological relevance. 2. We conducted a series of laboratory experiments and tested the dilution effect hypothesis in an amphibian-Batrachochytrium dendrobatidis (Bd) system and tested for consistency between our laboratory experiments and field patterns of amphibian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
118
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(124 citation statements)
references
References 48 publications
6
118
0
Order By: Relevance
“…Since the last step is the one relevant for climate change scenarios in our region (Philippart and Epping 2009), the net effect is likely to be a lowered transmission due to increased cercarial consumption. Field experiments and observations in our (Thieltges et al 2009) and other ecosystems (e.g., Upatham and Sturrock 1973, Mouritsen and Poulin 2003, Kaplan et al 2009, Venesky et al 2014) suggest that laboratory derived indications for predation effects of a variety of predators of free-living parasite stages hold true under field conditions. Hence, the observed temperature-predation interaction is likely to translate into a compensation of elevated parasite production under climate change.…”
Section: Discussionmentioning
confidence: 58%
“…Since the last step is the one relevant for climate change scenarios in our region (Philippart and Epping 2009), the net effect is likely to be a lowered transmission due to increased cercarial consumption. Field experiments and observations in our (Thieltges et al 2009) and other ecosystems (e.g., Upatham and Sturrock 1973, Mouritsen and Poulin 2003, Kaplan et al 2009, Venesky et al 2014) suggest that laboratory derived indications for predation effects of a variety of predators of free-living parasite stages hold true under field conditions. Hence, the observed temperature-predation interaction is likely to translate into a compensation of elevated parasite production under climate change.…”
Section: Discussionmentioning
confidence: 58%
“…When systematic changes in the abundance of small mammals occur following wildlife decline (as observed following experimental defaunation), this may cause increases in the risk of many rodent-borne diseases (Ostfeld andHolt 2004, Young et al 2014). Conversely, for zoonotic diseases that have high host specificity, and are primarily frequency dependent, changes in community composition and species richness observed under more intensive types of land-use conversion, particularly in agricultural sites, will likely have more profound impacts than any changes in density (Venesky et al 2013, Lacroix et al 2014. For example, several species that appear to thrive in agricultural land-uses (e.g., M. natalensis, A. nairobae) March 2015 357 CONTEXT-DEPENDENT EFFECTS OF LAND-USE are known to be excellent hosts for several regionally important human pathogens (Oguge et al 1997), and thus agricultural landscapes will likely increase prevalence of pathogens primarily hosted by these species.…”
Section: Synthesismentioning
confidence: 99%
“…This is of particular interest in light of increasing interest in the effects of human disturbance and host diversity on levels of parasitism and particularly on disease transmission. Multiple studies have argued that high host diversity and low levels of anthropogenic disturbance tend to lead to lower intensities and prevalence of parasitism and disease in a wide range of systems (Keesing et al, 2010;Haas et al, 2011;Lacroix et al, 2014;Venesky et al, 2014), with vector-borne diseases in rodents being one important study system (LoGiudice et al, 2003;Friggens and Beier, 2010). However, other studies have failed to find a causal relationship (Giraudoux et al, 2013;Oda et al, 2014), or they have found idiosyncratic relationships across hosts, parasites, and environmental conditions (Froeschke et al, 2013;Salkeld et al, 2013;Young et al, 2013a;Kedem et al, 2014).…”
Section: Across Populationsmentioning
confidence: 99%